Anthropological Perspectives on Children as Helpers, Workers, Artisans, and Laborers - Lancy, David F. (Palgrave Studies on the Anthropology of Childhood and Youth, 2018)
Within academia, the study of childhood has been dominated by a mono-cultural or WEIRD (Western, educated, industrialized, rich, and democratic) perspective. However, a contrasting and more varied perspective is emerging within the field of anthropology. So, while the phenomenon of children as workers is ephemeral in WEIRD societies and in the literature on child development, there is ample cross-cultural and historical evidence of children making vital contributions to the family economy. Children's "labor" is of great interest to researchers but it is treated as extra-cultural-an aberration that must be controlled. Work as a central component in children's lives, development, and identity goes unappreciated. This book aims to rectify that omission by surveying and synthesizing a very robust corpus of material. Two prominent themes receive particular emphasis: the processes involved in learning to work, and the interaction between ontogeny and children's roles as workers.